Dampak regulasi pajak digital terhadap kepatuhan keuangan platform UMKM online - Dini Khoirani; Ajeng Tita Nawangsari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the impact of digital tax regulation and digital tax literacy on the financial compliance of online Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The main issue addressed is the relatively low fiscal compliance level within the rapidly growing digital economy sector, despite the government’s implementation of digital-based tax policies. This research employs a quantitative approach with an explanatory research design to examine the causal relationships among variables. Primary data were collected through an online survey of 385 MSME owners operating on e-commerce platforms such as Tokopedia, Shopee, and Bukalapak. The research instrument consisted of a closed-ended questionnaire using a five-point Likert scale, tested for validity through Confirmatory Factor Analysis (CFA) and for reliability using Cronbach’s Alpha (>0.7). The results of multiple linear regression analysis show that digital tax regulation (β = 0.426; p < 0.001) and digital tax literacy (β = 0.337; p < 0.001) both have a positive and significant influence on MSMEs’ financial compliance. The coefficient of determination (R² = 0.482) indicates that these two variables explain 48.2% of the variance in financial compliance levels. These findings confirm that effective digital tax policies and higher levels of tax literacy play crucial roles in enhancing compliance among online business actors. This research provides practical implications for the government to strengthen the integration between digital tax systems and e-commerce platforms, while also improving tax literacy through technology-based education programs. Theoretically, the findings reinforce the Theory of Planned Behavior as a framework for understanding tax compliance behavior in the digital era and offer empirical evidence for developing inclusive and adaptive fiscal policies aligned with the digitalization of the economy.